Ethical Climate(s), Distributed Leadership, and Work Outcomes: The Mediating Role of Organizational Identification - Barattucci, Massimiliano; Teresi, Manuel; Pietroni, Davide; Iacobucci, Serena; Lo Presti, Alessandro; Pagliaro, Stefano (Frontiers in Psychology, 2021)
Organizational Identification (OI) has increasingly attracted scholarly attention as a key factor in understanding organizational processes and fostering efficient human resource management. Available evidence shows that organizational ethical climate crucially predicts OI, a key determinant of both employees’ attitudes and behaviors. In the present paper, we examined the relationship between two specific ethical climates (self-interest vs. friendship), Distributed Leadership (DL), employees’ attitudes and behaviors, incorporating OI as a core underlying mechanism driving these relationships. Three hundred and forty-two employees filled out questionnaires to examine the ethical climate, DL, OI, a series of measures concerning attitudes and behaviors towards the organization. Structural equation modeling confirmed that a perception of an ethical climate of friendship (but not self-interest) fostered OI, which elicited higher commitment, perceived trust and recommendation, and lower turnover intention. Perception of DL further contributed to increasing OI. Our findings suggest that HR practices should carefully consider employee perceptions of a collectivistic (vs. individualistic) ethical climate, together with perceptions of DL, as key determinants of positive organizational outcomes. We discuss results in light of the Social Identity Approach and present practical implications for HR management.